Sodium hypochlorite solution penetration into human dentine: a histochemical evaluation. (17th April 2016) - Giardino, L.; Cavani, F.; Generali, L.
Abstract: Aim: The aim of this study was to evaluate ex vivo the penetration depth of sodium hypochlorite solutions, with and without surfactants, into human dentine using a histochemical stain and the bleaching ability of NaOCl. Methodology: Extracted maxillary central incisors were decoronated and their root canals were shaped to a size 30, .07 taper. Dentinal tubules were stained with 10% copper sulphate solution followed by a 1% rubeanic acid alcohol solution under vacuum. Specimens were irrigated with 5 mL of Niclor 5 (5.25% NaOCl solution) or 5 mL of Hypoclean (5.25% NaOCl solution + surfactants) according to the corresponding treatment group, for 2 min. A transverse section was obtained in the middle portion of the apical, middle and coronal thirds of each tooth. Under microscopic examination, irrigant penetration was evaluated by measuring the following: the bleached circumference of the root canal with respect to the stained circumference; bleached areas, mean and maximum penetration depth. For statistical analysis, Pearson's chi‐squared test and one‐wayanova were used. Results: Only 30% of dentine tubules in the apical portions were stained; therefore, these were excluded from further comparisons. In the middle and coronal thirds, the average bleached circumference of the root canal was 80–99% of the stained circumference and the bleached area was 73757–135107 μm 2 . The average penetration depth ranged from 39 to 62 μm and maximum penetration from 74 to 131 μm. For all reported results, no differences within and between groups were observed ( P = 1). Conclusion: No differences in penetration of irrigants with and without surfactants into dentinal tubules were observed in the middle and coronal thirds of incisor teeth.